2018
DOI: 10.1016/j.ntt.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to tobacco and cannabis: Effects on autonomic and emotion regulation

Abstract: Tobacco and cannabis are often used together in pregnancy and both have effects on children's regulatory system. Yet, little is known about the impact of co-use on the development of emotion regulation at the developmentally salient age of 2 years. One pathway linking co-exposure to tobacco and cannabis to toddler regulation may be via poor autonomic regulation in infancy. In addition, substance using mothers may be more dysregulated themselves, which may have direct effects on toddler regulation, but may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 71 publications
3
28
0
1
Order By: Relevance
“…Moreover, MJ+TOB co-exposure was associated with nearly 200% increased impact versus TOB exposure alone on self-soothing and need for examiner soothing. Results complement a recent MJ+TOB co-exposure study which revealed associations between coexposure and less adaptive autonomic regulation in nine-month old infants (Eiden et al, 2018). Results also complement prior studies of TOB-exposure alone, which showed increased irritability, alterations in regulatory processes and increased need for external soothing across the first postnatal month (Espy et al, 2011; Stroud et al, 2009a; Stroud et al, 2009b; Yolton et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, MJ+TOB co-exposure was associated with nearly 200% increased impact versus TOB exposure alone on self-soothing and need for examiner soothing. Results complement a recent MJ+TOB co-exposure study which revealed associations between coexposure and less adaptive autonomic regulation in nine-month old infants (Eiden et al, 2018). Results also complement prior studies of TOB-exposure alone, which showed increased irritability, alterations in regulatory processes and increased need for external soothing across the first postnatal month (Espy et al, 2011; Stroud et al, 2009a; Stroud et al, 2009b; Yolton et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…Despite plausible neurobiological mechanisms and evidence for increased maternal and neonatal health risks from prenatal MJ+TOB exposure, few studies examined the impact of prenatal co-use on infant neurobehavioral development. Eiden et al found that MJ+TOB coexposure was associated with less adaptive autonomic regulation at nine months, which was then associated with diminished emotion regulation at twenty-four months (Eiden et al, 2018). Schuetze et al investigated prenatal MJ+TOB co-exposure effects on infant reactivity and regulation in the context of maternal and fetal mediators (maternal stress, anger, fetal growth) (Schuetze et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, heart rate showed an age‐related decrease for both baseline and emotion‐evoking tasks whereas RSA showed an age‐related increase for both baseline and emotion‐evoking tasks, regardless of task valence. This review was both necessary and timely to review existing literature for assessing internal responses to emotion in childhood, as emotion regulation has implications for later functional outcomes (Carpenter & Tomasello, 2000; Mundy & Sigman, 2006; Weiss et al., 2014; Woods & Wetherby, 2003), and is a focus of much recent research attention, including in children at risk for mental health disorders (e.g., Eiden et al., 2018) and neurodevelopmental disorders (Sheinkopf et al., 2019). Understanding the potential differences that may arise due to methodological and analytical differences can inform future studies as researchers continue to investigate emotional regulation and reactivity differences in typically developing children and children with an atypical presentation.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for duplication was to explore task, age, and measurement effects broadly. Data from the same study were included if they compared baseline to emotion‐evoking task (a) at different time points (e.g., ages; n = 9; Zeegers et al., 2017), (b) by characteristic (e.g., sex; n = 1; Eiden et al., 2018), (c) across different tasks ( n = 6; e.g., Calkins et al., 1998a), or (d) provided both HR and RSA data ( n = 7; e.g., Busuito et al., 2019). Note that one study (Calkins & Keane, 2004) provided data across different ages, tasks, and measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Maternal prenatal SUD increases infants' ER problems that typically emerge as soothing difficulties, inflexible and narrow repertoire of stress regulation, high physical reactivity, and negative emotionality, evidenced among children exposed to cocaine (Eiden et al, 2009;Mayes et al, 1996), cannabis and tobacco (Eiden et al, 2018), and methamphetamine (LaGasse et al, 2012;Smith et al, 2015). Neonatal abstinence syndrome is common among newborn exposed to opioid drugs and relates to irritability and high-pitched crying that are also indicators of ER problems (Fodor et al, 2014).…”
Section: Maternal Substance Use and Children's Emotion Regulationmentioning
confidence: 99%